PENGARUH TIPS DAN TRIK DALAM PERENACANAAN KARIR MELALUI LAYANAN INFORMASI KEPADA SISWA KELAS XI DI SMA NEGERI 4 BANJARMASIN - Siswanto, Adi; Jarkawi, Jarkawi; Farial, Farial (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2019)
work, what professions are suitable for him and so forth. The above problems we often find in schools especially in high school, As has happened in high school SMA Negeri 4 Banjarmasin, teachers BK said there are still many students who are still confused in determining the department and career or what work is chosen later for the future, this is due to lack or BK teachers never provide career information services to students. Based on data analysis shows that there are significant differences in understanding of career planning of class XI students before and after service information that is giving tips and tricks career planning. This is true from the results of the initial test (Pre Test) with an average of 129.12 increased after being given Treatment through information service by providing career planning tips and tricks which then performed the final test (Post Test) with an average of 139.72. Then the initial test difference with the final test is 10.6. Thus, information services with the provision of career planning tips and tricks can be used as a very effective means in determining career planning students XI SMA Negeri 4 Banjarmasin.